Determinants of infant and young child feeding practices in Rupandehi, Nepal - Gautam, Kapil Prasad (BMC Res Notes, 2016)
BACKGROUND: Undernutrition is a major problem in Nepal and meeting the minimum dietary standard is essential for growth and development of young children. Continuous monitoring of such practices is important to inform policy and program formulation. This study aimed to assess complementary feeding practices, and associated factors in Western Nepal. METHODS: This was a cross-sectional study conducted in Rupandehi district of Western Nepal. Face-to-face interviews were conducted among 178 mothers of young children aged 6–23 months using a structured questionnaire and data on complementary feeding practices. These practices were reported as frequency distribution and the factors associated were ascertained using multiple logistic regression. RESULTS: Only 57 % of mothers initiated complementary feeding at the age of 6 months. While the proportion of young children receiving minimum meal frequency was reasonably high (84 %), meal diversity (35 %) and minimum acceptable diet (33 %) remained low. Maternal education and having had their children’s growth monitored were independently associated with receiving minimum acceptable diet. CONCLUSION: Few infants and young children received the recommended infant and young children feeding practices. Implementing health promotion programs that educate and enhance the skills of mothers should be a priority for future nutrition interventions.